1983
DOI: 10.1111/j.1365-2125.1983.tb02171.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of pinacidil in hypertension.

Abstract: In a balanced single‐blind placebo controlled study in six hypertensive patients treated with diuretic and beta‐adrenoceptor blocker, a single oral dose of 10 mg pinacidil lowered blood pressure significantly, by a maximum of 26/13 mm Hg lying and 15/12 mm Hg standing at 3 h. The duration of action was less than 6 h. Chronic treatment of four patients (mean dose 20 mg twice daily for 3–7 weeks) lowered blood pressure by only 15/7 mm Hg. All four patients experienced side‐effects of the type often observed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This suggests that the side effects were not dose related. These observations on the frequency of side effects, and the shorter duration of action after chronic administration correspond very closely to those of Ramsay & Freestone (1983) and Ward (1984) in their studies with the original pinacidil formulation. Pinacidil appears to produce a tachycardia, particularly at night.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This suggests that the side effects were not dose related. These observations on the frequency of side effects, and the shorter duration of action after chronic administration correspond very closely to those of Ramsay & Freestone (1983) and Ward (1984) in their studies with the original pinacidil formulation. Pinacidil appears to produce a tachycardia, particularly at night.…”
Section: Discussionsupporting
confidence: 83%
“…A single-blind study of the effects of pinacidil in hypertension revealed There were two 48 h periods of intra-arterial BP typical vasodilator side effects whilst the BP recording, separated by 4 to 6 weeks' dose titrareduction lasted less than 6 h (Ramsay & tion of pinacidil. During the first 24 h the patients Freestone, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Carlsen et al (1981) reported pinacidil to be remarkably free from side effects. In a four patient trial in which pinacidil in the present tablet formulation was added to bendrofluazide with atenolol (Ramsay & Freestone, 1983) three patients had adverse effects whilst taking 20 mg twice daily, and one whilst taking 30 mg twice daily. The same authors reported that after 10 mg of pinacidil a hypotensive effect was detectable at 4 but not at 6 h, and questioned the usefulness of twice daily dosing.…”
Section: Resultsmentioning
confidence: 90%
“…It augmented the hypotensive effect of hydrochlorothiazide (Muiesan et al, 1983), and was effective and well tolerated alone in a 4 week open trial (Carlsen et al, 1983). A placebo controlled trial, with pinacidil as third agent to diuretic and ,-adrenoceptor blocker, was abandoned however because of adverse effects (Ramsay & Freestone, 1983 Figure 1. Doses above 20 mg daily increased mean pulse rate, but only significantly at 7 and 9 weeks in the erect position (P < 0.05).…”
Section: Introductionmentioning
confidence: 99%
“…Pinacidil is a potassium channel opener which has been shown to be an effective antihypertensive drug in man (Kardel et al, 1981;Ramsay & Freestone, 1983). This is due to the drug's potent vasodilating properties.…”
Section: Discussionmentioning
confidence: 99%